An inquiry concerning Japanese yen interest rate swap yields - Tanweer Akram; Khawaja Abdullah al Mamun (Levy Economics Institute of Bard College, 2023)
This paper econometrically models Japanese yen (JPY)-denominated interest rate swap yields. It examines whether the short-term interest rate exerts an influence on the long-term JPY swap yield after controlling for several key macroeconomic variables, such as core inflation, the growth of industrial production, the percentage change in the equity price index, and the percentage change in the exchange rate. It also tests whether there are structural breaks in the dynamics of Japanese swap yields and related variables. The estimated econometric models show that the short-term interest rate exerts an important influence on the long-term swap yield in some periods but not in other periods in which core inflation exerts a marked influence on the swap yield. The findings from the econometric models reveal a discernable relationship between the call rate and the swap yield of different maturity tenors clearly held prior to April 2014 but did not in the subsequent period. These findings highlight the limits and scope of John Maynard Keynes's contention that the central bank's policy rate commands a decisive influence over the long-term market rate through the short-term interest rate. The policy implications of the estimated models' results are discussed.
Keywords: E43; E50; E58; E60; G10; G12; 330; Interest Rate Swaps; Swap Yields; Call Rate; Inflation; Bank of Japan (BOJ); Japan